Relevansi Asas Kebebasan Berkontrak dalam Konteks Ekonomi Digital - Vivilia Agnata Mudi; Magdhalena Tasik Todingrara (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The principle of freedom of contract is a fundamental concept in civil law that provides parties with the autonomy to form, determine the content of, and implement an agreement. However, the development of information and communication technology has brought about the phenomenon of the digital economy, which has transformed patterns of contractual relationships, particularly through electronic contracts. The characteristics of digital contracts uniform, instantaneous, and generally expressed in standard clauses raise the question of the extent to which the principle of freedom of contract remains relevant. This article aims to analyze the concept of freedom of contract in civil law, its application in the digital economy, and to assess its relevance in addressing contemporary legal challenges. The research employs a normative juridical method with statutory, conceptual, and comparative approaches. The findings indicate that the principle of freedom of contract continues to hold relevance, but its application cannot be understood in absolute terms. In the digital context, the principle requires reinterpretation by taking into account contractual justice and consumer protection.